Independent value of serum β-human chorionic gonadotropin in predicting early pregnancy loss risks in IVF/ICSI cycles - Wang, Liyan; Jiang, Yanbiao; Shen, Haofei; Ma, Xiaoling; Gao, Mingxia; Jin, Panpan; Zhang, Rui; Zhao, Lihui; Zhang, Xuehong (Frontiers in Immunology, 2022)
Background: Early pregnancy loss(EPL) is the most common complication of pregnancy, especially in couples undergoing assisted reproductive technology treatment. The present study aimed to determine whether the serum β-human chorionic gonadotropin (β-hCG) level after 14 days of embryo transfer, either alone or in combination with other parameters in IVF/ICSI cycles, could be used to predict subsequent EPL. Methods: This was a retrospective cohort study conducted on all couples who received clinical pregnancy and underwent fresh IVF/ICSI cycles between January 2013 and June 2020 at a single large reproductive medical center. A total of 6600 cycles were included in this study. Univariate and multivariate logistic regression analyses were performed to evaluate relevant risk factors for EPL. Receiver operating characteristic (ROC) curves were generated, and areas under the curve (AUC) were calculated and compared between β-hCG and other factors. Results: β-hCG level was considerably lower in women who occurred EPL than in those who were ongoing pregnancy(564.03 ± 838.16 vs 1139.04 ± 1048.72 IU/L, p< 0.001). Univariable and multivariable logistic regression revealed that β-hCG levels were significantly correlated with the risk of EPL, independent of other risk factors. More importantly, β-hCG level could independently predict the occurrence of EPL and was comparable to the model that combined other risk factors. The optimal cut-off value of serum β-hCG level for predicting EPL was 542.45 IU/L. Conclusions: Our results showed that serum β-hCG level had a strong independent predictive value for EPL occurrence in fresh IVF/ICSI cycles.